Genomic studies of Alzheimer’s disease: history, progress, and future directions - Naj, Adam Christian (Henry Stewart Talks, 2018)
Alzheimer’s disease (AD): pathology, epidemiology and risk factors, Genetics of AD: early-onset AD (EOAD) & late-onset AD (LOAD), Future genomic studies of AD